EVALUATION OF RENOPROTECTIVE EFFECT OF CILNIDIPINE IN PATIENTS WITH MILD TO MODERATE HYPERTENSION AND TYPE 2 DIABETES MELLITUS – A PROSPECTIVE STUDY - R, RAMYA; OM, SHAJAHAN; KALADHARAN, ANAKHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to evaluate the renoprotective effect of cilnidipine by estimating urinary albumin and creatinine levels in mild-to-moderate hypertension (HTN) with type 2 diabetes mellitus (DM) and also evaluate the adverse drug profile of cilnidipine in the same patients. Methods: This was a single-center, prospective, open-labeled, randomized study. A total of 60 patients of either gender aged between 30 and 60 with mild-to-moderate HTN with type 2 DM were included in the study. Urine albumin and urine creatinine were measured at day 1 and day 181. Blood pressure (BP) was measured in all visits. The drug cilnidipine at a dose of 10–20 mg oral was given and the corresponding improvement in the levels of urine albumin and other parameters was identified. Results: There was a significant reduction in the mean systolic BP from 150.07±5.44 mmHg in visit 0 to 123.03±5.23 mmHg in visit 3. And also, there was a significant reduction in the mean diastolic BP from 95.5±8.15 mmHg in visit 0 to 80.8±2.42 mmHg in visit 3. The mean heart rate at visit zero was 76.71±4.86. At the end of 6 months of treatment, there was a significant reduction to 70.63±2.74. There was a significant reduction in the microalbuminuria from 66.62±8.39 to 38.8±6.45. The mean reduction was 27.56±10.25. There was no change in the creatinine level. Conclusion: The study reveals that the drug cilnidipine is safe and effective in reducing the microalbuminuria and also effectively reduces BP in hypertensive patients. Hence, the drug cilnidipine can be safely administered to the patient with diabetes and HTN.